Land use change impacts on European heat and drought: remote land-atmosphere feedbacks mitigated locally by shallow groundwater. (2nd April 2019) - Zipper, Samuel C; Keune, Jessica; Kollet, Stefan J
Abstract: Heat and drought are projected to increase globally but may be mitigated or exacerbated by land use/land cover (LULC) change. Here, we show that remote land-atmosphere feedbacks caused by historical European LULC change led to widespread changes in the energy and water balances, drought, and heat. Using a continental-scale bedrock-to-atmosphere model, we find that LULC change following the Soviet Union collapse and European Union formation may have substantially increased cloud cover and decreased incoming shortwave radiation in western Europe, even in locations where LULC did not change. These changes to the water and energy balances had spatially heterogeneous impacts on drought and heat, including drying in the Mediterranean and Eastern Europe regions. The response of the water and energy balances to remote feedbacks was lessened in areas with shallow groundwater, indicating that local- and continental-scale responses to LULC change are influenced by the coupling between the subsurface, land surface, and atmosphere.